Natural wound dressing films prepared from acetylated starch/κ-carrageenan blend incorporated with mandelic acid - Wimolsiri SRIPHOCHAI; Jutarat Prachayawarakorn (Journal of Metals Materials and Minerals, 2024)
Due to several limitations of acetylated starch film for wound dressing applications such as low mechanical properties and no antibacterial activity, acetylated starch film was, therefore, modified by different contents of κ-carrageenan and mandelic acid. Infrared spectra confirmed the presence of κ-carrageenan and mandelic acid in the modified acetylated starch films. In addition, the decreased crystallinity of the carrageenan modified acetylated starch films led to more smooth film, as observed by scanning electron images. Besides, the addition of various amounts of κ-carrageenan in the modified acetylated starch films caused the improvement of mechanical properties, moisture uptake, water vapor transmission rate (WVTR), and degree of swelling. Moreover, κ-carrageenan modified acetylated starch film loaded with 20 wt% of mandelic acid exhibited antibacterial property against both S.aureus and E.coli bacteria. Additionally, degree of crystallinity, mechanical properties, moisture uptake, WVTR, degree of swelling, antibacterial activity, and cytotoxicity of κ-carrageenan modified acetylated starch films added by different amounts of mandelic acid were also studied.
Keywords: Seaweed-derived Bioactive Compounds; Wound Healing and Treatments; Food and Agricultural Sciences